Prognostic Implications of Decorin, E-Cadherin and EGFR Expression in Inflammatory and Non-Inflammatory Canine Mammary Carcinomas - Gouveia, Bethânia Almeida; Ramos, Fernanda Ramalho; Silva, Ingrid Kester Lima; Oliveira, Thalita Evani Silva de; Vasconcelos, Rosemeri de Oliveira [UNESP]; Xavier, José Guilherme; Strefezzi, Ricardo Francisco (Wiley, 2025)
Inflammatory mammary carcinoma (IMC) is the most aggressive variant of invasive mammary tumours in dogs and in women. Decorin is an extracellular matrix molecule whose expression can be reduced or absent in various human cancers, which is associated with a poor prognosis. E-cadherin is a cell adhesion protein whose expression is reduced in several neoplasms. However, it is overexpressed in inflammatory breast cancers of women. EGFR is also associated with cancer development and is commonly overexpressed in aggressive neoplasms. This study aimed to characterise the expressions of Decorin, E-cadherin, and EGFR in canine inflammatory and non-inflammatory mammary carcinomas (IMC and non-IMC) and to evaluate their expression levels as prognostic indicators for survival and occurrence of metastases. Thirty-three IMC and 43 non-IMC cases were analysed retrospectively and submitted to immunohistochemical analysis. The reactions were quantified in five high-power field images from areas of the highest intensity and frequency of immunostaining (hot spots). We found significantly lower expression of Decorin and higher of E-cadherin and EGFR in canine IMCs. Patients with tumours that exhibited Decorin expression in less than 26.35% of epithelial cells had shorter survival (p = 0.0410) and a higher occurrence of distant metastases (p = 0.0115). E-cadherin is overexpressed in canine IMCs (p < 0.0001), similar to what occurs in women, reinforcing that dogs can be used as a study model for human IMC. EGFR overexpression in canine IMCs (p = 0.0322) provides evidence for potential targeted therapy with tyrosine kinase inhibitors.
Keywords: biomarker; cancer; dog; extracellular matrix; immunohistochemistry; prognosis